Beyond Market Proximity: Gender, Market Access, and Socioeconomic Resilience Among Small-Holders of Patchouli Farmers in Indonesia - Moralitha Mazya, Thita (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
Despite persistent socioeconomic challenges in Indonesia’s aromatic crop sector, gender dynamics within the patchouli value chain remain underexplored. This study analyses the socioeconomic resilience of smallholder farmer households by highlighting the interrelationships among gender governance, market access, and adaptive strategies in the patchouli (Pogostemon cablin) value chain in Sulawesi, Indonesia. Primary data from 287 respondents in ten villages was collected through focus group discussions (FGDs) and interviews with 30 key informants. Data collection was conducted using a systematic random sampling method. This study investigated the relationship between gender roles and household resilience using the Gender-Sensitive Value Chain (GSVC) framework and correlation analysis. The results show that women's participation is significant throughout the value chain. However, they are still not involved in strategic decision-making. This indicates continuing structural gender-based inequality in the agricultural production system. With higher resilience scores (r = 0.32, p < 0.01), women's involvement in household financial management was positively correlated with resilience scores. This shows that women make a significant, but often unrecognized, contribution to household adaptive capacity. This study shows that for a competitive and sustainable aromatic crop economy, policies that empower women in the patchouli value chain, promote local institutions, and improve financial literacy are essential.